Ethnicity, N. 2 : Politics of Recognition - Vladislav, Volkov (Daugavpils Universitātes Sociālo pētījumu institūts, Latvijas Universitātes Filozofijas un socioloģijas institūts, 2010)
The articles published in this issue analyse various forms of politics of recognition concerning ethnic identities as Poles and Russians and other ethnic minorities in connection to Latvia.
"Ethnicity" is a peer-reviewed journal that was established by the Institute of Social Investigations (Daugavpils University, Latvia) and the Institute of Philosophy and Sociology (University of Latvia). The journal publishes original works about ethnicity in different fields of knowledge – sociology, history, social linguistics, social psychology, law, political science.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Ethnology; ethnic identity; multiethnic society; Latvian jews; ethnic minority; «Latvian Jews and the Soviet Power in 1928–1953» - book review